2022
DOI: 10.3390/s22051936
|View full text |Cite
|
Sign up to set email alerts
|

The Improved WNOFRFs Feature Extraction Method and Its Application to Quantitative Diagnosis for Cracked Rotor Systems

Abstract: During its operation, a rotor system can be exposed to multiple faults, such as rub-impact, misalignment, cracks and unbalancing. When a crack fault occurs on the rotor shaft, the vibration response signals contain some nonlinear components that are considerably tougher to be extracted through some linear diagnosis methods. By combining the Nonlinear Output Frequency Response Functions weighted contribution rate (WNOFRFs) and Kullback–Leibler (KL) divergence, a novel fault diagnosis method of improved WNOFRFs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…However, for early bearing wear, the vibration signal of the bearing lacks obvious fault characteristics [ 25 , 26 ]. The bearing wear cannot be detected effectively only by the vibration signal [ 27 ]. Aiming at the insufficiency of a single type of sensor, the fault diagnosis method based on multi-sensors has been gradually developed [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, for early bearing wear, the vibration signal of the bearing lacks obvious fault characteristics [ 25 , 26 ]. The bearing wear cannot be detected effectively only by the vibration signal [ 27 ]. Aiming at the insufficiency of a single type of sensor, the fault diagnosis method based on multi-sensors has been gradually developed [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The stability and effectiveness of index J were verified through numerical model and tests were conducted on the rotor with rub-impact. Liang et al 26,27 proposed the approach of improved WNOFRFs based on the KL divergence and the associated index KLRm to diagnose the rotor rub-impact and cracks. The results of numerical models and experiments indicate that KLRm can quantitatively diagnose crack faults of rotor systems.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in displacement and vibration frequency can be taken as defect indicators. To this end, many authors have suggested using indicators of the nonlinear behavior of the cracked shaft, such as the natural frequency and the orbits, in order to detect the presence of cracks [17][18][19][20][21][22][23][24]. The reduction of the the critical speed turns out to be a very good indicator of the presence of cracks [25] in rotating shafts.…”
Section: Introductionmentioning
confidence: 99%